Tahapan Pengembangan dan Perubahan SDM di Lembaga Dakwah - M Gustar Umam; Cecep Castrawijaya (CV. ITTC INDONESIA, 2025)
Human resource (HR) development and transformation are vital components for the success of Islamic missionary (dakwah) institutions. Unlike profit-oriented organizations, dakwah institutions focus on conveying Islamic values that balance material and spiritual aspects. This article explores the challenges and stages of HR development within dakwah institutions, including recruitment processes, initial orientation, and advanced training programs. It highlights key challenges such as limited financial resources, leadership regeneration, and the demands of digital transformation. The study outlines both internal and external recruitment strategies, the importance of values- and competency-based selection, and the necessity of training in Islamic preaching, communication, management, digital media, and leadership. A structured and continuous HR development process enhances the effectiveness and professionalism of dakwah institutions, ensuring their relevance in a changing era and enabling strategic engagement with digital-native audiences. This study aims to provide practical insights for dakwah management in building a competent and competitive human resource system.